2021
DOI: 10.1111/ggi.14223
|View full text |Cite
|
Sign up to set email alerts
|

Association between social frailty as well as early physical dysfunction and exercise intolerance among older patients receiving hemodialysis

Abstract: Background Recently, social frailty has been increasingly recognized as a factor associated with adverse health outcomes, including physical disability and mortality. However, there are no studies about the importance of this factor among hemodialysis patients. Therefore, we investigated the relationship between social frailty and early physical dysfunction in this group of patients. Methods This was a two‐center cross‐sectional study. Older patients receiving hemodialysis were prospectively enrolled. Moreover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
(33 reference statements)
1
7
0
Order By: Relevance
“…This study investigated the associations of frailty phenotypes and the number of frailty components with exercise capacity. Our previous study reported that frailty was associated with a lower peakVO 2 than non‐frailty, including the phenotypes robust and pre‐frail, 26 while HD patients with frailty in the present study showed a significant decrease of peakVO 2 compared with patients with pre‐frail and robust phenotypes. In addition, peakVO 2 had a declining trend with an increased number of frailty components, and the frailty phenotype and number of frailty components were associated with peakVO 2 .…”
Section: Discussionsupporting
confidence: 45%
See 2 more Smart Citations
“…This study investigated the associations of frailty phenotypes and the number of frailty components with exercise capacity. Our previous study reported that frailty was associated with a lower peakVO 2 than non‐frailty, including the phenotypes robust and pre‐frail, 26 while HD patients with frailty in the present study showed a significant decrease of peakVO 2 compared with patients with pre‐frail and robust phenotypes. In addition, peakVO 2 had a declining trend with an increased number of frailty components, and the frailty phenotype and number of frailty components were associated with peakVO 2 .…”
Section: Discussionsupporting
confidence: 45%
“…However, physical function is not the sole factor related to exercise capacity and frail. Our previous study in HD patients without frailty reported that patients with social frailty had lower peakVO 2 and physical function compared with those without social frailty 26 . In addition, social isolation of the older population has been reported to be associated with the progression of frailty 34 .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Heart rate (HR) was continuously monitored and blood pressure was measured every minute during CPX. Peak work rate (WR) and peak HR were recorded during CPX, and chronotropic index (%) was evaluated using the following equation: chronotropic index (%) = (peak HR − rest HR)/(220 − age − rest HR) × 100 ( Usui et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…It is also emphasized by advising health care providers, family members, and mental health providers on the purpose of social support for this group of patients. Research conducted by Usui N et al (15) showed patients who received dialysis treatment may involve social weakness.…”
Section: Theme Ii: Environmental Supportmentioning
confidence: 99%